Tomato mottle mosaic virus: Characterization, resistance gene effectiveness, and quintuplex RT-PCR detection system - Carlos Kwesi TETTEY; Zhi-yong YAN; Hua-yu MA; Mei-sheng ZHAO; Chao GENG; Yan-ping TIAN; Xiang-dong LI (Journal of Integrative Agriculture, 2022)
Tomato mottle mosaic virus (ToMMV), an economically important species of the genus Tobamovirus, causes significant loss in yield and quality of tomato fruits. Here, we identified the Shandong isolate of ToMMV (ToMMV-SD) collected from symptomatic tomato fruits in Weifang, Shandong Province of China. ToMMV-SD caused symptoms such as severe mosaic, mottling, and necrosis of tomato leaves, yellow spot and necrotic lesions on tomato fruits. The obtained full genome of ToMMV-SD was 6 399 nucleotides (accession number MW373515) and had the highest identity of 99.5% with that of isolate SC13-051 from the United States of America at the genomic level. The infectious clone of ToMMV-SD was constructed and induced clear mosaic and necrotic symptoms onto Nicotiana benthamiana leaves. Several commercial tomato cultivars, harboring Tm-22 resistance gene, and pepper cultivars, containing L resistance gene, were susceptible to ToMMV-SD. Plants of Solanum melongena (eggplant) and Brassica pekinensis (napa cabbage) showed mottling symptoms, while N. tabacum cv. Zhongyan 100 displayed latent infection. ToMMV-SD did not infect plants of N. tabacum cv. Xanthi NN, Brassica rapa ssp. chinensis (bok choy), Raphanus sativus (radish), Vigna unguiculata cv. Yuanzhong 28-2 (cowpea), or Tm-22 transgenic N. benthamiana. A quintuplex RT-PCR system differentiated ToMMV from tomato mosaic virus, tomato brown rugose fruit virus, tobacco mosaic virus, and tomato spotted wilt virus, with the threshold amount of 0.02 pg. These results highlight the threat posed by ToMMV to tomato and pepper cultivation and offer an efficient detection system for the simultaneous detection of four tobamoviruses and tomato spotted wilt virus infecting tomato plants in the field.